2004
DOI: 10.1029/2004gl020192
|View full text |Cite
|
Sign up to set email alerts
|

Transient ion beamlet injections into spatially separated PSBL flux tubes observed by Cluster‐CIS

Abstract: [1] Ion measurements from Cluster-CIS were used to characterize and interpret the signatures of PSBL energydispersed ions and their fine structure. On 14 February 2001, several ion injections were encountered by SC 1 and SC 3, separated by $530 km, during an outbound orbit at 4.5 R E . Both satellites recorded the same ion structures. The energy dispersion of each ion structure was dominated by the timeof-flight effect (TDIS). In addition, we show evidence for spatial properties of the ion injections: (1) SC 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 9 publications
2
50
0
Order By: Relevance
“…5.7 Association with poleward arcs of double oval As previously reported, both events occurred during a double auroral oval and the footprints of the beamlets mapped into the vicinity of the poleward arcs (Keiling et al, 2004b). The conjugacy of ion beamlets and auroral activity begs the question whether the ions were responsible for the auroral emissions.…”
Section: Association With Facmentioning
confidence: 78%
See 3 more Smart Citations
“…5.7 Association with poleward arcs of double oval As previously reported, both events occurred during a double auroral oval and the footprints of the beamlets mapped into the vicinity of the poleward arcs (Keiling et al, 2004b). The conjugacy of ion beamlets and auroral activity begs the question whether the ions were responsible for the auroral emissions.…”
Section: Association With Facmentioning
confidence: 78%
“…Since we argued above that the edges of ion beamlets were associated with the heating of the ion conics, one might expect that the ion conics would be displaced from the edges due to this E×B drift which however was not observed. In Keiling et al (2004b) it was concluded that the edges of ion beamlets on 14 February 2001 were caused by a distant tail source which itself convected with the E×B drift, thus creating a broad energy range on the same field line (see also Lennartsson et al, 2001). Therefore, the E×B drift of the source regions of both magnetotail beamlets and ion conics -both located on the same flux tubescould explain why no separation of beamlets and ion conics occurred.…”
Section: Generation Of Ion Conicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The pitch-angle spectrograms of the ions in the PSBL (bottom three panels) show that the ions are field-aligned, and all measurements come from the pitch-angle bins closest to the magnetic field direction. Important features on this day include time-dispersed ion injections observed in all ion species beginning around 00:44 UT, previously studied by Keiling et al (2004), who showed that the injection included four to five "beamlets" separated by ∼ 100 s. Injections of the lower-energy ions of ∼ 1 keV occurred in coincidence with these beamlets. As the spacecraft entered into the inner boundary of the PSBL (after 00:55 UT), higher-energy ions and inverted-V structures were observed; see Cui et al (2014) for further discussion of these inverted-V events.…”
Section: Observationsmentioning
confidence: 99%